Studi Emisi Tungku Masak Rumah Tangga - Agus Haryanto; Sugeng Triyono (agriTECH, 2012)
The objective of this research was to study emission characteristic of household stoves. Five stoves were tested, namely clay pot biomass stove, brick biomass stove, kerosene stove, coal stove, and LPG stove.  Emission parameters to be measured were CO, NO2, SO2, and particulates. Gas emission was measured using gas analyzer Wolfsense TG 501, while particulate was determined based on Indonesian National Standard (SNI: 19-7117.12-2005). Results showed that LPG stove emitted no CO indicating that complete burning existed. Other stoves emitted CO with kerosene stove exhibited the highest CO emission of 1074 μg/m3. Biomass pot stoves produced SO2 (722 μg/m3) which is lower than LPG stove (1488 μg/m3) and kerosene stove (1055 μg/m3), but higher than coal stove (290 μg/m3). On the other side, biomass pot stoves produced more NO2 (99 μg/m3 with pot stove) as compared to kerosene stove (25 μg/m3). Particulate emission increased based on the fuels used with an order from the lowest was LPG stove, kerosene stove, coal stove, and biomass stove.ABSTRAKTujuan penelitian ini adalah untuk mengkaji karakteristik emisi beberapa tungku atau kompor dapur rumah tangga. Penelitian dilakukan dengan menggunakan lima jenis tungku atau kompor, yaitu tungku biomassa pot tebal, tungku biomassa bata, kompor minyak tanah, kompor batubara, dan kompor LPG. Parameter emisi yang diukur meliputi CO, NO2, SO2 dan partikel. Emisi gas diukur menggunakan gas analyser Wolfsense TG 501, sedangkan emisi partikel debu ditentukan berdasarkan standar SNI 19-7117.12-2005. Hasil penelitian menunjukkan bahwa kompor LPG tidak menghasilkan emisi CO. Kompor minyak tanah menghasilkan emisi CO paling tinggi yaitu (1074 μg/m3). Kompor LPG menghasilkan emisi SO2 paling banyak (1488 μg/m3), diikuti kompor minyak tanah (1055 μg/m3), tungku kayu pot (722 μg/m3), dan kompor batubara (290 μg/m3). Di pihak lain, tungku biomassa pot tebal menghasilkan NO2 lebih banyak (99 μg/m3) dibandingkan kompor minyak tanah (25 μg/m3). Emisi partikulat meningkat menurut jenis bahan bakar yang digunakan dengan urutan dari yang paling rendah adalah LPG, minyak tanah, batubara, dan biomassa.